Spiritualitas Dalam Perspektif Agama-Agama: Sebuah Pencarian Titik Temu - Labib Marzuki Shobir (Universitas Islam Tribakti Lirboyo Kediri, 2020)
Religion carries an important aspect from which it functions as a vehicle for humans to act on how to carry out our lives in this world. This condition tends to bring religion to the exclusive side. In social life, religion used to have conditions where all structures were built properly. Basically, the